Acute cholecystitis as a sign of occult metastatic gastric cancer: case report and review of the literature - Montali, Filippo; Grandi, Luca; Rastelli, Francesca; Impellizzeri, Sebastiano Giuseppe; Martinez, Julieta Lucia; Alfredo, Annicchiarico; Virgilio, Edoardo; Renato Costi, Renato Costi (Acta Biomedica Atenei Parmensis, 2024)
Acute cholecystitis (AC) is a frequent clinical condition, usually related to biliary lithiasis. In a very poor cases, AC can be caused by tumor infiltration and distant metastasis. Gallbladder represents an uncommon site of tumor metastasis, mostly from melanoma and clear cell renal tumor. Gastric cancer has rarely been reported to metastasize to the gallbladder. Herein we present a very singular case of a lithiasic AC which turned out to be a metastatic gastric cancer in a previously healthy man. We also offer a review of the pertinent literature.